«Una gestazione lunga e travagliata»: la fondazione delle Università di Sassari e Cagliari. - TODDE, ELENA (Scripta, 2020)
The slow process of foundation of the University of Sassari and Cagliari saw the two Sardinian cities committed to obtaining a higher education school for their young people. The long «gestation» was accompanied by numerous parliamentary requests, the spasmodic search for funding, the competition for recognition as the first university in the kingdom and the relationship with the Society of Jesus, which represented the first step towards an academic education. This contribution reconstructs the process of university education from the first demands made in the Parliament chaired by Viceroy Antonio de Cardona to the royal privileges of the first half of the 17th century.